Ethics and Politics - Macintyre, Alasdair (Cambridge University Press, 2006)
Alasdair MacIntyre is one of the most creative and important philosophers working today. This volume presents a selection of his classic essays on ethics and politics collected together for the first time, focussing particularly on the themes of moral disagreement, moral dilemmas, and truthfulness and its importance. The essays range widely in scope, from Aristotle and Aquinas and what we need to learn from them, to our contemporary economic and social structures and the threat which they pose to the realization of the forms of ethical life. They will appeal to a wide range of readers across philosophy and especially in moral philosophy, political philosophy, and theology.